2009
DOI: 10.1258/ijsa.2009.009077
|View full text |Cite
|
Sign up to set email alerts
|

What service users want: a new clinic results service. Can we satisfy both patients' needs and wants?

Abstract: Many clinics still have a 'no news is good news' (NNIGN) policy for clinic results. We asked our service users their preferences for obtaining results. We also designed a new clinic results service. Patients were invited to complete a service evaluation questionnaire. They were given nine options for obtaining results and asked to rate acceptability on a 1-9 scale (unacceptable to acceptable). Completed questionnaires were compared with the actual method they chose to obtain results for that visit. In all, 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Smartphones can not only facilitate communication between patients and their physicians, but can also create new ways to provide patients with disease education, and connect them to a variety of resources in their communities. 10,11,12 Smartphones and other mHealth tools also offer a unique advantage in that they can provide easy, anonymous, and comparatively inexpensive access to people irrespective of their cultures, languages, incomes, or geographical locations.…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones can not only facilitate communication between patients and their physicians, but can also create new ways to provide patients with disease education, and connect them to a variety of resources in their communities. 10,11,12 Smartphones and other mHealth tools also offer a unique advantage in that they can provide easy, anonymous, and comparatively inexpensive access to people irrespective of their cultures, languages, incomes, or geographical locations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients are receptive to receiving messages related to appointment or medication reminders and health-related messages via email or Short Message Service (SMS; i.e., text message). One survey of 1000 adults found that mobile phone was the favored method of receiving medical test results, 5 and studies of persons of low socioeconomic status 6 and those with chronic illnesses 7 have found that they are receptive to receiving messages related to appointment or medication reminders and health-related education through these methods. Parents have also expressed openness to receiving health-related messages about their children.…”
Section: Introductionmentioning
confidence: 99%